Spatial Analysis of the River Line and Land Cover Changes in the Kampar River Estuary: The Influence of the Bono Tidal Bore Phenomenon - Putra, Aprizon; Wisha, Ulung Jantama; Kusumah, Gunardi (Universitas Muhammadiyah Surakarta, 2017)
The Kampar River estuary is well known for a tidal-bore phenomenon called âBono wavesâ. The emergence of Bono waves has a significant influence on the estuary system of Kampar River. Scoured materials, resulting from the hydraulic jump of the tidal bore, are carried into the middle of the river. These materials are then deposited when the velocity of the river decreases as a result of the collision of the tidal current from the sea and the river flow. The aim of this was to determine the area of erosion and sedimentation with respect to the river line and perform land-cover change analysis for the area around the Kampar River estuary for the years of 1990, 2007, 2010 and 2016. The method employed was the supervised maximum likelihood (SML) classifications, which uses an overlay technique to yield alternate information on the river line and land-cover changes in the form of time-series data. The largest erosion occurred during 1990â2007, for which the average change reached 2.36 ha/year. The smallest erosion occurred during 2010â2016, when the change reached 0.41 ha/year. The largest land-cover change was found during 1990â2016, which occurred in the land for agriculture/plantations (11.57 ha/year), building/settlement (48.11 ha/year) and scrubland (30.88 ha/year). The other types of land cover, such as bare land and sediment deposition, varied every single year. The changes to the river line are caused by land-cover changes, and the Bono waves that lead to erosion and sedimentation that is not stable in the middle of the river and downstream.